Pengaruh Absensi Biometrik (Fingerprint), Motivasi Kerja dan Kompensasi Financial terhadap Disiplin Kerja - Putra, Kompiang Gede Agus Darma; Wimba, I Gusti,Ayu; Adwitya Sanjaya, Putu Krisna (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
The purpose of this study was to determine the effect of biometric attendance (fingerprints), work motivation and financial compensation on the work discipline of village officials at Pemecutan Kaja Village Office, North Denpasar District, Denpasar City. The population in this study were 37 respondents. The sampling technique in this study uses saturated sampling or census sampling, where all members of the population are sampled. The data analysis technique used is multiple linear regression analysis. The test results show that Biometric Attendance (fingerpint), Work Motivation and Financial Compensation have a positive and significant effect on Work Discipline of Village Apparatus at Pemecutan Kaja Village Office, North Denpasar District, Denpasar City, either partially or simultaneously. The advice that can be given is that the Pemecutan Kaja Village Office is expected to conduct an analysis within the institution, always unite, review, and improve the implementation of the existing attendance system, increase open communication between fellow village officials and provide additional income. to the village apparatus based on objective considerations.